Effect of sintering conditions and microstructure on the magnetostrictive properties of cobalt ferrite - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2008)
The effects of sintering temperature and dwell time on the magnetostrictive properties of polycrystalline cobalt ferrite synthesized by the conventional ceramic method have been investigated. The present study showed that the magnitude of magnetostriction strongly depends on the microstructure of the final sintered product. The presence of small and uniform grains with less porous structure in the sintered material leads to enhancement of the magnetostrictive strain. Higher magnetostriction is obtained for samples sintered at a relatively lower temperature of 1100 degrees C. These results are further corroborated by analyzing the effect of some additives during sintering on the microstructural and magnetostrictive properties.